2018
DOI: 10.17235/reed.2018.5408/2017
|View full text |Cite
|
Sign up to set email alerts
|

Quality indicators in colonoscopy. The colonoscopy procedure

Abstract: The aim of the project this paper is part of was to propose quality and safety procedures and indicators to facilitate quality improvement in digestive endoscopy units. In this second issue, procedures and indicators are suggested regarding colonoscopy. First, a diagram charting the previous and subsequent steps of colonoscopy was designed. A group of experts in health care quality and/or endoscopy, under the auspices of the Sociedad Española de Patología Digestiva (SEPD), performed a qualitative review of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 46 publications
0
1
1
1
Order By: Relevance
“…Although the literature proves a relationship between bowel cleansing and adenoma detection (Gálvez et al, 2017;Sánchez-del-Río et al, 2018), this study found no significant intergroup differences in that regard. Our data were consistent with studies (Gálvez et al, 2017;Rembacken et al, 2012) that included patients undergoing their first colonoscopies, and which found that an educational video on bowel cleansing was effective.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Although the literature proves a relationship between bowel cleansing and adenoma detection (Gálvez et al, 2017;Sánchez-del-Río et al, 2018), this study found no significant intergroup differences in that regard. Our data were consistent with studies (Gálvez et al, 2017;Rembacken et al, 2012) that included patients undergoing their first colonoscopies, and which found that an educational video on bowel cleansing was effective.…”
Section: Discussioncontrasting
confidence: 85%
“…This present study analyzed the outcomes of colon cleansing based on BBPS scores, the presence of adenoma, and cecal intubation. A previous related study proposed necessary procedures and indicators of structure, process, and results when applying and evaluating colonoscopy quality, thus finding 13 specific indicators; of these, the quality of intestinal cleansing was characterized as a process indicator because it facilitates the detection of a colon adenoma-an outcome indicator (Sánchez-del-Río et al, 2018). Cecal intubation was also considered an outcome indicator because it enabled the quantification of colonoscopies resulting in complete colon exploration (Sánchez-del-Río et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…O preparo intestinal adequado é um fator determinante para a capacidade de realização do exame, assim como a duração do procedimento (Andrade et al, 2020). Isso auxilia também o diagnóstico e as abordagens terapêuticas necessárias, pois possibilita a realização do exame de forma segura, com a introdução do aparelho sob visão direta, evitando que lesões passem despercebidas (Andrade et al, 2017;Guinhazi et al, 2019;Sánchez-del-Río et al,2018).…”
Section: Introductionunclassified